Analysis of individual performance indicators of football goalkeeper - Alberto Tienza-Valverde; Víctor Hernández-Beltrán; Mario C. Espada; Alfredo Bravo-Sánchez; Fernando J. Santos; José M. Gamonales (Elsevier, 2023)
One of the most widely used strategies for performance analysis in different sports is notational analysis through direct observation of technical-tactical actions, which allows to understand the main indicators of sporting performance of the players, both individually and collectively. Football goalkeepers (GKs) are involved in the game differently when compared to the rest of the players in the team and, therefore, they develop different high-level and high-intensity tactical-technical actions. Therefore, the present work aimed to analyse the different performance indicators of football GKs through a search in the following databases: Web of Science (WOS), Scopus (Elsevier), PubMed (NIH) and, SPORTDiscus (EBSCO), until February 2023. The following keywords were used: ''Football'' or ''Soccer'', ''Goalkeeper'' and ''Performance analysis''. The results show that the main performance indicators are the percentage of avoided goals, the distribution of the ball at the goal kick as well as the number of offensive and defensive actions. Therefore, training sessions should be planned and implemented aimming to improve these skills.